Configuring Cisco AVVID - Syngress Media, Inc. (Rockland, Mass. : Syngress Media ; London : Harcourt Brace (distributor), 2000)
What is AVVID? Previously called Configuring Cisco Communications Networks (CCN), Architecture for Voice, Video, and Integrated Data (AVVID) is the latest development from Cisco Systems that will soon redefine the way businesses communicate. AVVID allows businesses to transmit voice, data, and video over one combined architecture, whereas in the past, three separate systems were required. Configuring Cisco AVVID will be the first book to discuss the components of the AVVID architecture and will be timed to release with the launch of the technology in early 2000. A practical guide to the AVVID technology this book will include an introduction to AVVID, and its software, hardware, network architecture, installation, operation and configuration. Topics include CallManager, Cisco Gateways, and IPCC (Cisco IP Contact Center). * The first book to discuss the components of this important new technology * Practical guide; many engineers will find this a great source of AVVID product knowledge * Cisco is planning to launch AVVID hardware and software in Spring 2000 - demand is already high for information * Book will be timed to release with technology.
An Introduction to AVVID Technology -- An Overview of AVVID Hardware Solutions -- Migrating Your Network to AVVID Technologies -- Configuring Cisco CallManager -- Utilizing AVVID Applications and Software Solutions -- Utilizing Unified Messaging and Active Voice -- Design Considerations in a WAN/Campus Environment -- The Cisco AVVID Fast Track -- Appendix: Optimizing Network Performance with Queuing and Compression
Includes index.
Keywords: Computer network architectures; Electronic books